2015
DOI: 10.3126/jcmc.v4i3.11930
|View full text |Cite
|
Sign up to set email alerts
|

Oral health related knowledge, attitude, and practice among school children of Jyamrung, Nepal

Abstract: Oral diseases are common in school children of underprivileged region of developing countries. The community-based oral health promotion approach, using schools as a platform, is a way to tackle the oral health problems of community with limited human and financial resources. A base-line study was conducted in a school of Jyamrung so as to evaluate oral health related knowledge, attitude and practices among schoolchildren, based on which an oral health promotion program will be developed for the school. A desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The Oral health knowledge attitude and behavior among monks and nuns were good as compared to other students from government schools of Nepal with same age groups [12][13][14]. Dental caries prevalence in permanent dentition seems more as compared to Lee et al14 and similar with Shakya et al,12 this might be due to lack of regular oral practices, education and dental service provision. Another study done among monks and nuns…”
mentioning
confidence: 79%
“…The Oral health knowledge attitude and behavior among monks and nuns were good as compared to other students from government schools of Nepal with same age groups [12][13][14]. Dental caries prevalence in permanent dentition seems more as compared to Lee et al14 and similar with Shakya et al,12 this might be due to lack of regular oral practices, education and dental service provision. Another study done among monks and nuns…”
mentioning
confidence: 79%
“…Student’s oral health knowledge was scored using a system adopted from previous studies (7,8) Oral health knowledge was determined by asking the following questions (1) periodontal disease can affect health, (2) regular tooth brush can protect tooth decay, (3) fizzy soft drinks affect the teeth, (4) use of fluorides prevent tooth decay, (5) gingivitis is a disease that makes your gums bleed, (6) causes of dental caries or proper tooth brushing can prevent dental caries (7) sugar causes tooth decay, (8) tooth decay is a disease that destroys your teeth, and (9) healthy teeth means strong and carries free teeth. Oral health practices were determined by asking the following questions: (1) frequency of brushing teeth, per day, (2) time spent for brushing in minute, (3) cleansing aid used, (4) materials used to clean teeth, (5) frequency of changing tooth brush, (6) type of toothpaste used, (7) mouth rinsing after eating, (8) clean tongue after meal or during rushing.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 58% of schoolchildren aged between 5-6 years were affected by dental caries according to report by the National Pathfinder Survey, 2004. Another study found that oral health related problems was the prime reason of missing school in Nepal where32% of the students missed their school due to dental pain (6).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is available about the association of oral health problems with oral hygiene practices and sociodemographic factors. A study conducted in Nepal has shown that socio-economic factors and poor oral health practices resulted in oral health problems [ 10 ]. Another study has also shown that gingival bleeding was common in children in rural areas [ 11 ].…”
Section: Introductionmentioning
confidence: 99%